SOOT a Case Study on Women and Video Games - Céspedes Vindas, Adriana (2024)
The way in which certain groups are represented in the audiovisual media is important. Video games, as an immersive multimediaresource, are not exempt from gender stereotypes. The purpose of this article is to describe the methodology to create characters for the Costa Rican video game SOOT. To do this, a methodological process of compilation and theory on the subject in the narrative area was followed. Then, using examples from the video game, the design methodology is described, a mixture derived from Ellis and Bratman’s models. In addition, the archetypes of the female characters, the game, and the hero’s journey among the main characters are explored from a narrative perspective. It is important to explore more this topic with other case studies to improve the representation not only of women but also of other minorities in video games.